Size and persistence matter: Wage and employment insurance at the micro level - Martin Kerndler (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2019)
Firms provide substantial insurance against wage fl uctuations and job loss. This paper studies how the interaction between shock size and persistence affects the firm's ability to insure workers against idiosyncratic firm-level shocks. Using linked employer-employee data from Germany, I find that wages respond largely symmetrically to positive and negative permanent shocks. Whereas transitory shocks lead to upward wage rigidity. Individual layoff probabilities only increase in response to negative permanent shocks. Interestingly, wage cuts and job loss after negative shocks are limited to blue-collar workers. Whereas white-collar workers are fully insured against negative shocks both in terms of wages and employment.
Keywords: C33; D22; J33; J41; 330; wage insurance; layoffs; linked employer-employee data; Kalman filter